Transcriptional and epigenetic rewiring by the NUP98::KDM5A fusion oncoprotein directly activates CDK12 - Selina Troester; Thomas Eder; Nadja Wukowits; Martin Piontek; Pablo Fernández-Pernas; Johannes Schmoellerl; Ben Haladik; Gabriele Manhart; Melanie Allram; Margarita Maurer-Granofszky; Nastassja Scheidegger; Karin Nebral; et al. (Nature Communications)
Abstract Nucleoporin 98 (NUP98) fusion oncoproteins are strong drivers of pediatric acute myeloid leukemia (AML) with poor prognosis. Here we show that NUP98 fusion-expressing AML harbors an epigenetic signature that is characterized by increased accessibility of hematopoietic stem cell genes and enrichment of activating histone marks. We employ an AML model for ligand-induced degradation of the NUP98::KDM5A fusion oncoprotein to identify epigenetic programs and transcriptional targets that are directly regulated by NUP98::KDM5A through CUT&Tag and nascent RNA-seq. Orthogonal genome-wide CRISPR/Cas9 screening identifies 12 direct NUP98::KDM5A target genes, which are essential for AML cell growth. Among these, we validate cyclin-dependent kinase 12 (CDK12) as a druggable vulnerability in NUP98::KDM5A-expressing AML. In line with its role in the transcription of DNA damage repair genes, small-molecule-mediated CDK12 inactivation causes increased DNA damage, leading to AML cell death. Altogether, we show that NUP98::KDM5A directly regulates a core set of essential target genes and reveal CDK12 as an actionable vulnerability in AML with oncogenic NUP98 fusions.